2006
DOI: 10.1521/aeap.2006.18.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors and Sexual Risk in a Prospective Cohort of HIV-Positive Men and Women in New York City, 1994–2002: Implications for Prevention

Abstract: As an ever-increasing number of people infected with HIV are living longer, healthier lives, concerns about continued transmission are growing along with an awareness of the need to develop "prevention for positives." This study of HIV-positive adults in New York City is the first examination of patterns of sexual behavior in a large, representative cohort of HIV-infected individuals followed over an extended time period. A total of 968 HIV-positive adults were interviewed every 6-12 months between 1994 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 51 publications
6
43
1
Order By: Relevance
“…The movement into and out of periods of unsafe behavior is also apparent when we examine rates over time of unsafe sex with a woman partner for the continuing cohort of MSW who were interviewed all eight or seven of eight times from Wave 1 to Wave 8 (2002). Rates of unsafe sex for this subset of long term participants (n = 89) were 18% at baseline (1994), fluctuated up and down during the late 1990s (11, 15, 14, and 9% ), with a dip to 5% at Wave 6 (1999), followed by an increase to 10% at Wave 7(2000Wave 7( -2001 and again to 13% at Wave 8 (2002) (data not shown, see also Aidala et al 41 ).…”
Section: Sexual Risk Behaviorsmentioning
confidence: 68%
“…The movement into and out of periods of unsafe behavior is also apparent when we examine rates over time of unsafe sex with a woman partner for the continuing cohort of MSW who were interviewed all eight or seven of eight times from Wave 1 to Wave 8 (2002). Rates of unsafe sex for this subset of long term participants (n = 89) were 18% at baseline (1994), fluctuated up and down during the late 1990s (11, 15, 14, and 9% ), with a dip to 5% at Wave 6 (1999), followed by an increase to 10% at Wave 7(2000Wave 7( -2001 and again to 13% at Wave 8 (2002) (data not shown, see also Aidala et al 41 ).…”
Section: Sexual Risk Behaviorsmentioning
confidence: 68%
“…Other studies suggest that periods of sexual abstinence may be interspersed between other periods of sexual activity for some HIV-positive persons (e.g., Aidala et al 2006). These results, therefore, are not likely to represent life-long decisions in all, or even most, cases.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, a US national probability sample of PLWHA found that over 30% were sexually abstinent in the prior 6 months and nearly half of those reported that this was by choice (Bogart et al 2006). In a large New York City-based cohort, Aidala et al (2006) found that 58% of HIV-positive men and 65% of HIV-positive women reported that they were not sexually active for at least one 6-month period during the 10-year study. Other studies in the US have found rates of 6-month abstinence between 31% and 38% in HIV-positive samples (Reilly and Woo 2001;Wight et al 2000).…”
Section: Introductionmentioning
confidence: 87%
“…Indeed, such living situations are likely to obstruct the development of trust relationships and positive linkages, which increases the risks of chronicization and maintains homelessness among street-involved youth. 45 Building on others' work, 22,23,25,55,56 the present study longitudinally examined the occurrence of a variety of HIV risk behaviors in relation to changes in housing situation among street-involved youths. A major strength of this approach, based on mixed-effects regression, is that both risk behaviors and housing situations were allowed to vary not only across study participants but also among them, which controlled for unmeasured potential individual confounders.…”
Section: Discussionmentioning
confidence: 99%